KONSEP BISNIS TANPA HUTANG DARI PEMIKIRAN TAQIYUDDIN ALNABHANI: THEMATIC ANALYSIS APPROACH - Rendra Fahrurrozie; Zulkarnain M. Ali; Bayu Taufik Possumah (Department Islamic Economics, 2022)
Purpose– The motivation of the purpose of writing this research is to get the concept of a debt-free business from the thoughts of Taqiyuddīn al-Nabhāni by exploring his book Nizhām al-Iqtishādy fī al-Islām and al-Syakhsiyyah al-Islāmiyyah Juz 2.Design/methodology/approach– The descriptive qualitative method is the methodology of this research with a thematic analysis approach and using atlas.ti software to help researchers categorize and provide themes and relationshipsbetween categories of the text being studied.Findings–. The results found in Taqiyuddīn Al-Nabhāni's thought research, there is a concept of the individual, public, and state ownership that becomes property without debt, which is divided into 3 categories namely work, giving, and optimization. From these assets, in Taqiyuddīn al-Nabhāni's thinking, they are developed through agriculture, trade, and industry, and are distributed according to sharia limits, namely obligatory distributions such as trade zakat or paying workers' wages, sunnah (recommended) distributions such as alms/infaq, or mubah (permissible) is to choose the main thing in advancing the business and avoiding the prohibited (haram) such as usury, maysir (gambling) or ihtikar (hoarding the basic goods needed).Research limitations/Implications– The limitation of this research is on loan debt (qardh) used by business people in developing their business and is limited by examining the thoughts of Taqiyuddīn Al-Nabhāni in his book Nizhām al-Iqtishādy fī al-Islām and al-Syakhsiyyah al-Islāmiyyah Juz 2. Originality/value– In including the literature of classical Islamic thought books from Taqiyuddīn Al-Nabhāni, this research contributes to providing solutions other than the debt that can be used by micro business entrepreneurs, or novice businessmen who will develop their wealth through business.Keywords- Islamic Economic Thought, Islamic Business, Zero-Debt, Taqiyuddīn Al-Nabhān